Hidrogeologi daerah BRG berdasarkan kondisi hidrologi untuk mengetahui prediksi kesetimbangan Airtanah (Groundwater) - Rohima Sera Afifah (INFO-TEKNIK, 2022)
The rapid increase in groundwater exploitation in various sectors in Indonesia has caused preparations in the form of concrete steps that must be faced, especially reducing the impacts caused. The BRG area is an area known as an area in Geological Conditions the existence of intrusions that may result in retained groundwater flows and are productively small and even rare and in addition to that also in terms of environmental conditions of areas surrounded by large industries in the amount of very large groundwater use. Groundwater intake activities impacted the drawdown of groundwater levels. This study in cased the Water Balance conditions of the BRG area groundwater. This study employs hydrology variable to determine groundwater balance. Variables of Rainfall (CH in mm/yr), Evapotranspiration (ET in mm/yr), Infiltration (R in mm/yr) and Run Off (RO in mm/yr). Balance of Groundwater is based on a general formula of Capacity (S). Capacity (S) is directly proportional to Rainfall (CH) as Inflow and Total amount of Evapotranspiration (ET), Infiltration (R) and Run Off (RO) as Outflow. The study revealed that the inflow and outflow of water in BRG area are balanced. The results of the Hydrological Variables of the study area are as follows: Rainfall (CH) is of 8302 mm/yr average value, Evapotranspiration (ET) is of 2726,6 mm/yr average value, Infiltration (R) is of 2,02 x 107 mm/yr and Run off (Ro) 1316,3 mm/yr. The result of Groundwater Water balance is a negative value (Inflow < Outflow). Hydrological calculations decreased in each year for the last 4 years the observation data showed the negative values were getting greater, as follows: (a) the first year -4.01 x 107, (b) the second year -5.63 x 107, (c) the third year -3.10 x 107, (d) the fourth year -4.72 x 107.